Quantitative determination of iodine content in iodized table salt marketed in Jordan as an indicator of compliance with national salt iodization standards: A cross-sectional study - Abughoush, Mahmoud; Olaimat, Amin N.; Al-Holy, Murad; Al-Awwad, Narmeen Jamal; Al-Dalali, Sam; Al-Hourani, Huda; Daseh, Lamees; Abazeed, Bushra; Al-Dabbas, Maher; Abuawad, Balkees; Abu-Ghoush, Laith; Al-Jawaldeh, Ayoub (Italian Journal of Food Science, 2024)
Iodine deficiency (ID) is a significant global public health issue, particularly affecting low-income countries. The iodization of salt is a widely adopted method to prevent iodine deficiency. This study aimed to assess the iodine content of iodized salt at the market level in various cities within the Hashemite Kingdom of Jordan (HKJ). We collected 152 salt samples from 24 different brands across three cities in Jordan: Amman, Zarqa, and Mafraq. The analysis was conducted using a titration method. The mean iodine content in salt samples varied by city, with values of 5.45 ppm in Mafraq, 10.33 ppm in Amman, and 13.22 ppm in Zarqa, ranging from 0 to 36 ppm. Significant differences in iodine concentration were observed within the same city across different brands (P ≤ 0.05). Additionally, variations were noted in iodine content for samples from the same brand collected in different cities, and even among samples from the same brand at the same location. Of the 152 samples evaluated, an average of 76.5% had iodine levels below the 15 ppm recommended by UNICEF. There was considerable variation in mean iodine content among brands, cities, and even within samples of the same brand. This indicates that the salt iodization process requires ongoing monitoring, and the government should enhance efforts to oversee the iodization process and improve the accessibility and utilization of iodized salt.